Nuclear receptor coregulators - Litwack, Gerald (Vitamins and Hormones, 2004)
First published in 1943, Vitamins and Hormones is the longest-running serial published by Academic Press.In the early days of the Serial, the subjects of vitamins and hormones were quite distinct.The Editorial Board now reflects expertise in the field of hormone action, vitamin action, X-ray crystal structure, physiology, and enzyme mechanisms.